O ambiente de acolhimento primário e sua influência na clínica do trauma - Slaviero, Amanda Riccioppo (2017)
The present work derived from the care of three patients who have common traits in their histories; all three suffered from adaptive faults to their needs during their early childhood. This theoretical-clinical study seeks to explore the themes of the primary care environments and regression to dependence in the care of traumatized patients, more specifically, those who suffered traumas early on during their first years. The purpose is to deepen the investigation about the consequences of these failures and its implications on other future object relations. I intend to discuss styles of analytical settings and clinical interventions that favour primary symbolization forms and creation of a potential space which allows re-signifying and reconstructing the experiences that could not be properly lived in early childhood. To understand the demands and to meet the needs of these patients, who present failures in the structuring and constitution of the self, this work proposes transference management forms, configuring the notion of therapeutic regression developed by Winnicott. This work discusses the need for such patients to be sustained to be able to re-launch their development process into new bases and a new beginning of psychic life